Aryl hydrocarbon receptor–ligand axis mediates pulmonary fibroblast migration and differentiation through increased arachidonic acid metabolism. (31st August 2016) - Su, Hsiang-Han; Lin, Hsin-Ting; Suen, Jau-Ling; Sheu, Chau Chyun; Yokoyama, Kazunari K.; Huang, Shau-Ku; Cheng, Chih Mei
Abstract: Pulmonary fibroblast migration and differentiation are critical events in fibrogenesis; meanwhile, fibrosis characterizes the pathology of many respiratory diseases. The role of aryl hydrocarbon receptor (AhR), a unique cellular chemical sensor, has been suggested in tissue fibrosis, but the mechanisms through which the AhR-ligand axis influences the fibrotic process remain undefined. In this study, the potential impact of the AhR-ligand axis on pulmonary fibroblast migration and differentiation was analyzed using human primary lung fibroblasts HFL-1 and CCL-202 cells. Boyden chamber-based cell migration assay showed that activated AhR in HFL-1cells significantly enhanced cell migration in response to 2, 3, 7, 8-tetrachlorodibenzo- p -dioxin (TCDD), and a known AhR antagonist, CH223191, inhibited its migratory activity. Furthermore, the calcium mobilization and subsequent upregulated expression of arachidonic acid metabolizing enzymes, including cyclooxygenase2 (COX-2) and 5-lipoxygenase (5-LOX), were observed in TCDD-treated HFL-1 cells, concomitant with elevated levels of prostaglandin E2 (PGE2) and leukotriene B4 (LTB4) secretion. Also, significantly increased expression of α-smooth muscle actin α-SMA), a fibroblast differentiation marker, was also noted in TCDD-treated HFL-1 cells (p < 0.05), resulting in a dynamic change in cytoskeleton protein levels and an increase in the nuclear translocation of the myocardin-related transcription factor. Moreover, the enhanced levels of α-SMA expression and fibroblast migration induced by TCDD, PGE2 and LTB4 were abrogated by selective inhibitors for COX-2 and 5-LOX. Knockdown of AhR by siRNA completely diminished intracellular calcium uptake and reduced α-SMA protein verified by promoter-reporter assays and chromatin immunoprecipitation. Taken together, our results suggested the importance of the AhR-ligand axis in fibroblast migration and differentiation through its capacity in enhancing arachidonic acid metabolism.